Analisis Peramalan Dengan Simulasi Monte Carlo dan Implementasi Pengendalian Persediaan Gula Berdasarkan EOQ - Oktavia, Chendrasari Wahyu; Sugioko, Andre (Metris: Jurnal Sains dan Teknologi, 2022)
Inventory control has an important role to maintain the stability of the company's business continuity. With inventory control, companies can meet consumer needs and consumers will feel satisfied if the demand comes on time. On the other hand, with this focus on inventory control, company management must also be careful if the raw material inventory is too large, it will result in high inventory costs, on the other hand, if there is too little raw material inventory, it will result in unfulfilled consumer needs. The purpose of this study is to identify forecasting the amount of sugar demand in 2019 and determine the amount of inventory costs from the forecasting results using EOQ. It is hoped that in the future the company will not only be able to know the future demand side based on forecasting, but the company already has an estimate of the total cost of inventory. The need for sugar raw materials from the forecasting results is 170,173 kg. Where the most needs are in April and November 2019, the number of economic purchases is 5218 kg with a frequency of ordering 33 times a year. Based on company policy, there is currently no information on safety stock and reoder points set by the company. With the EOQ proposal, the results of the safety stock and reoder point are 34,349 kg and 70,875 kg, respectively. The TIC proposal based on the EOQ is able to reduce the total inventory cost which was originally with the company's policy of Rp. 1,805,785,530 to Rp. 1,805,138,304 where this figure saves Rp. 647,226